Study The Economic and Social Impact of Museum Collections To The Local Tourism Industry, Including Increased Visits and Their Impact on Economic Growth District - Kusumaningrum, Anisa Putri; Sihombing, Cici Maria; Jorgi, Tomas; Andini, Davi Ayu (CV ODIS, 2023)
According to the desire of the community that the museum be an institution or centre of scientific research is expected to be able to always communicate the results of research to the community. Museum experts realize how important it is to conduct research activities in museums for the success of the analysis function of the museum itself, This study uses a qualitative approach. Because the problems discussed in this study are not about numbers. formulation of the problem in this study, How does the economic impact of museum collections on local tourism, How does the social impact of museum collections on local tourism and how does it affect regional economic growth? The results of this study social relations during this attraction are an excellent interaction.